Near‐Infrared Piezochromism from an o‐Carborane Dyad: Boron Clusters Facilitating a Wide‐Range Redshift and High Sensitivity. Issue 17 (20th February 2023) - Lv, Chunyan; Shen, Yunxia; Cao, Feng; Zhang, Qing; Wang, Kai; Zhang, Yujian
Abstract: Piezochromic materials, which exhibit a fluorescence response with large emission spectral shifts and high sensitivity, may be useful in important applications, but there have been few reports of such organic luminophores. Herein, we report a new high‐sensitivity piezochromic material based on the incorporation of an o ‐carborane unit, which exhibits aggregation‐induced emission properties. In a high‐pressure experiment, compared to carborane‐free MTY, which exhibits an emission spectral shift of 75 nm and a sensitivity of 19.1 nm ⋅ GPa −1, the o ‐carborane dyad MTCb shows a larger emission wavelength difference of 131 nm and a higher sensitivity of 32.8 nm ⋅ GPa −1, demonstrating a performance that ranks among the best of organic piezochromic materials reported thus far. MTCb molecules adopt a J‐aggregated pattern and have relatively loose molecular packing in the crystalline state. Interestingly, nonconjugated spherical carborane can disrupt the π‐π interactions between adjacent molecules during compression, which results in excellent piezochromic performance. Abstract : Spherical boron cluster . An o ‐carborane dyad (MTCb ) with a D‐π‐A architecture was developed as a high‐sensitivity piezochromic material. Compared to the carborane‐free MTY, the o ‐carborane dyad MTCb showed a larger emission wavelength difference of 131 nm and a higher sensitivity of 32.8 nm ⋅ GPa −1, resulting from the presence of icosahedral boron clusters.